Evaluating Financial Capability Services Provided in a Workforce Development Program. Issue 4 (17th July 2019) - Collins, J. Michael; Nafziger, Mia
Abstract : This field study explores the effects of an offer of financial counseling provided to low‐income people exiting welfare assistance in a workforce development program. While only about one‐third of workers actually took part in counseling, those who did were able to reduce the amount of debt they had in collections. We did not find other statistically significant effects on financial behavior or well‐being, however. People living at or below poverty levels of income may need more intensive financial support services than counseling can provide. This study illustrates the challenge of engaging participants in financial capability services, as well as the limitation of interventions like counseling for people who have very low incomes.